(untitled) (Principles and Practice of Clinical Research, 2022)
Introduction: Non-variceal upper gastrointestinal bleeding still poses a serious health problem due to high rebleeding rates, despite multiple treatment options. The relatively new over-the-scope clips® technique may be an effective alternative used in clinical practice and showed promising efficacy in predominantly observational studies. However, superiority over another mechanical technique as first-line therapy has not been established yet regarding initial hemostasis and recurring bleeding. Methods: The study will be a phase II, randomized, controlled, blinded, multicenter, parallel-group, superiority trial with a 1:1 allocation ratio. Adult patients with Ia-IIb Forrest classified ulcers will be randomized to either over-the-scope clips ® or through-the-scope clips. The primary outcome will be successful initial hemostasis and will be assessed by the endoscopist immediately after the procedure. Secondary outcomes will be rebleeding rate assessed by second-look endoscopy in case of substantial bleeding indicators, number of clips used, and mortality rate within 30 days. Further, the occurrence of adverse device effects will be assessed. Patient follow-up will occur periodically for a 3-month time frame. Discussion: By comparing two mechanical techniques for the treatment of common ulcers, our study will provide valuable grounds to deduce recommendations for first-line definite treatment and prevention of recurrent bleeding episodes. Trial registration: The trial will be registered at ClinicalTrials.gov (https://clinicaltrials.gov/). Keywords: upper gastrointestinal bleeding, hemostasis, bleeding control, OTSC, clinical trial